Pelatihan Penetapan Harga, Kelengkapan Fasilitas, Variasi Produk dan Kemampuan Manajerial Pada Pengelola Café di Kawasan Sembalun Lombok Timur - Sulhaini Sulhaini; Rusdan Rusdan; Rahman Dayani; B. Handayani Rinuastuti; Siti Nurmayanti (Universitas Mataram, 2023)
Cafe managers in Sembalun sub-district have weaknesess managerial skills, ownership of business facilities, pricing, product variations and marketing. Solving these problems is the main focus of this service activity. The solution to these problems is through training activities with materials that are in accordance with the problems faced and business assistance. The conclusion of this service activity is that the manager of the Cafe in the Sembalun area is still not professional; the managerial ability of the cafe business is low, not creative in product variations, pricing is not right, ownership of facilities is still limited, and generally does not have a coffee blending professional (barista). Important results of the community service is that the team provide suggestions as follows; (1) price issues; (a) Do cost classifications based on the main function in manufacturing companies, (b) Determine the cost of goods, namely the cost of production, cost of goods sold, and selling price. (2) The problem of product variation, it is necessary to develop product variations both in terms of product lines and product items by means of; (a) use raw materials from agricultural products in the Sembalun area which are relatively large for food or beverage products. (b) Add a variety of products other than the core product (3) Facility problems, to provide more facilities, (4) managerial skills problems, a cafe manager must have high spirit, and competences and (5) Need to form groups/associations as a means to develop promotion.